Advertising and sales promotion (Himalaya, 2015)
Is one of the key aspects of Marketing management, the functional area of management, and it is vast and big area of study and never ending process too. the need for effective marketing is as strong as ever in today's highly competitive and global business environment The challenge for academic and practitioners alike is how best to apply the principles of advertising in the area of marketing to secure strategic advantage. This book offers adequate and uptodate information on the current marketing challenges and problems to be faced by the marketing managers in advertising of their product and services. In fact such challenges must be viewed as golden opportunities to be capitalized by marketers with help of integrated plans and strategies. Such plans and timely responses can easily secure best rapport with dynamic economic and social demands and deliver rich dividend to marketing enterprises